Design Of Energy-Efficient Clustering Algorithm for Large Scale Wireless Sensor Networks (International Journal of Engineering and Computer Science, 2015)
A wireless sensor network (WSN) is a network system comprised of spatially distributed devices using wireless sensor nodes with limited energy resources. The individual nodes are capable of sensing their environments, processing the information data locally, and sending data to one or more collection points in a WSN. That issue can be solve by using clustering algorithm as a solution to reduce energy consumption. The System implements a clustering method for entire networks. The nodes are organized into clusters. Within a cluster, nodes transmit data to cluster head (CH) without using . CHs transmit data to sink. In this paper, a new clustering algorithm, named PDKC, is proposed for wireless sensor networks based on node deployment knowledge. In PDKC , sensor node location is modelled by Gaussian probability distribution function instead of using GPSs or any other location-aware devices. Finally, we present a distributed implementation of the clustering method. Extensive simulations confirm that our method can reduce the number of transmissions significantly and shows corresponding time delay.